Donadinia echinacea and Plectania sichuanensis, two novel species of Sarcosomataceae from southwestern China - Zeng, Ming; Gentekaki, Eleni; Hyde, Kevin D.; Zhao, Qi (Phytotaxa, 2021)
This paper describes five sarcosomataceous samples collected from southwestern China and provides an updated two locus phylogeny of Sarcosomataceae. Two new species, Donadinia echinacea and Plectania sichuanensis, are described based on morphological and phylogenetic analyses. Donadinia echinacea is a dematiaceous hyphomycete with pleurogenous, guttulate conidia. Plectania sichuanensis is a cup-fungus distinguished by its ochre hymenium and ellipsoid ascospores with small multiple oil droplets. Phylogenetic analysis based on ITS and LSU sequence data using broad taxon sampling supports establishment of the new species along with eight distinct clades within Sarcosomataceae.